The chemistry and efficacy benefits of polysaccharides from Atractylodes macrocephala Koidz - Liu, Congying; Wang, Shengguang; Xiang, Zedong; Xu, Tong; He, Mengyuan; Xue, Qing; Song, Huaying; Gao, Peng; Cong, Zhufeng (Frontiers in Pharmacology, 2022)
Atractylodes macrocephala (AM), traditional Chinese medicine (TCM) with many medicinal values, has a long usage history in China and other oriental countries. The phytochemical investigation revealed the presence of volatile oils, polysaccharides, lactones, flavonoids, and others. Atractylodes macrocephala polysaccharide (AMP) is one of its important medicinal components, mainly composed of glucose (Glc), galactose (Gal), rhamnose (Rha), arabinose (Ara), mannose (Man), galacturonic acid (GalA) and xylose (Xyl). It also showed valuable bioactivities, such as immunomodulatory, antitumour, gastroprotective and intestinal health-promoting, hepatoprotective, hypoglycaemic as well as other activities. At the same time, based on its special structure and pharmacological activity, it can also be used as immune adjuvant, natural plant supplement and vaccine adjuvant. The aim of this review is to summarize and critically analyze up-to-data on the chemical compositions, biological activities and applications of AMP based on scientific literatures in recent years.